Impact of COVID-19 on Women, Pregnancy and Psychologically - Sharleen Khan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Gender differences among the responses to the COVID-19 disease needs to studied. Aspandemic is growing and more and more cases are being registered, correlation between disease and genderresponse if any should be examined.Summary: pandemic of COVID-19 is evolving which reported its first case in Wuhan, PRC, considerableamount and efforts are only directed towards containment of the virus. The effect of the pandemic on pregnantwomen physiologically, psychologically and classification by socioeconomic status can give better trendsto study. Further mortality rate between men and women and reason behind it can be evidently proved afterthrough study. After all, one solution to different problems cannot be implemented. Middle East respiratorysyndrome (MERS) and Severe Acute respiratory syndrome (SARS) also belonging to similar family of thecoronavirus have more things to study regarding which strategy should be employed in containing the viralspread. Vertical transmission is not seen yet but occurrences of sporadic deaths of infants or still birth couldbe explained after research.Conclusion: Gender based case fatality rate and its reasons can be extremely helpful in treating the patientwith specific gender. Psychological state in the time of distress always been a cause of worry. It worries morewhen identified in pregnant state. All these aspects need to studied thoroughly